Kurtosis index to characterise near line‐of‐sight conditions in reverberating chambers. Issue 3 (1st February 2013) - Sorrentino, Antonio; Ferrara, Giuseppe; Migliaccio, Maurizio
Abstract : In this study, the kurtosis index, k, is first applied to the phase of the electromagnetic field within the reverberating chamber (RC) to characterise near line‐of‐sight (near LOS) conditions. This k approach is time effective and granular enough to characterise this working region. A large set of experiments accomplished at the RC of the Università di Napoli Parthenope, formerly Istituto Universitario Navale, demonstrate the effectiveness of the new index.